Inherited and acquired vitamin B12 deficiencies: Which administration route to choose for supplementation? - Elangovan, Ramyia; Baruteau, Julien (Frontiers in Pharmacology, 2022)
Vitamin B12 or cobalamin deficiency is a commonly encountered clinical scenario and most clinicians will have familiarity prescribing Vitamin B12 to treat their patients. Despite the high prevalence of this condition, there is widespread heterogeneity regarding routes, schedules and dosages of vitamin B12 administration. In this review, we summarise the complex metabolic pathway of Vitamin B12, the inherited and acquired causes of Vitamin B12 deficiency and subsequently highlight the disparate international practice of prescribing Vitamin B12 replacement therapy. We describe the evidence base underpinning the novel sublingual, intranasal and subcutaneous modes of B12 replacement in comparison to intramuscular and oral routes, with their respective benefits for patient compliance and cost-saving.